Improving Service Levels in the Hotel Industry through a Lean Service Model: A Case Study - Ampuero Rodas, Ana (2024)
Companies in the hotel sector aim to offer a high level of service to their customers. However, factors such as cleanliness and customer service make it challenging to obtain the expected results. For this reason, an operations model was developed that combines Lean tools such as 5S, Poka Yoke, and standardized work tools to increase customer satisfaction in a hotel in Cuzco, Peru. The results obtained from implementing the model through a pilot test and a simulation test using Arena software proved the model's performance since the Satisfaction Level increased from 78.48 to 80.13 and the Net Promoter Score from 24.22% to 33.22%. This research concludes that the proposal increases the satisfaction of the company's customers, which translates into higher revenues. It is also significant in providing valuable information for Peru's hotel and tourism sector, thus improving the industry's quality and competitiveness. © 2024 Latin American and Caribbean Consortium of Engineering Institutions. All rights reserved.